2007
DOI: 10.1128/jvi.01880-06
|View full text |Cite
|
Sign up to set email alerts
|

White Spot Syndrome Virus Annexes a Shrimp STAT To Enhance Expression of the Immediate-Early Gene ie1

Abstract: Although the Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway is part of the antiviral response in arthropods such as Drosophila, here we show that white spot syndrome virus (WSSV) uses a shrimp STAT as a transcription factor to enhance viral gene expression in host cells. In a series of deletion and mutation assays using the WSSV immediate-early gene ie1 promoter, which is active in shrimp cells and also in insect Sf9 cells, an element containing a STAT binding motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(104 citation statements)
references
References 47 publications
4
98
2
Order By: Relevance
“…3B). An increase in promoter activity following the deletion of this region was also observed in another study (7), suggesting that a negative element is present here. Furthermore, after mutation of the YY1 sequence in the full-length promoter, despite the absence of LvYY1 in cells, the promoter plasmid exhibited transactivation activity that was higher than that of the wild-type construct.…”
Section: Discussionsupporting
confidence: 54%
“…3B). An increase in promoter activity following the deletion of this region was also observed in another study (7), suggesting that a negative element is present here. Furthermore, after mutation of the YY1 sequence in the full-length promoter, despite the absence of LvYY1 in cells, the promoter plasmid exhibited transactivation activity that was higher than that of the wild-type construct.…”
Section: Discussionsupporting
confidence: 54%
“…Although the complete sequence of the WSSV genome has been known for several years (7,55,60), knowledge of the biological functions of the viral proteins is still quite poor. The WSSV immediate-early gene ie1 (31) was recently shown to use a shrimp signal transducer and activator of transcription (STAT) as a transcription factor to enhance its expression and contribute to its high promoter activity in host cells (30). In the present study, we further investigate the characteristics of WSSV IE1.…”
mentioning
confidence: 97%
“…Briefly, the Sf9 insect cells were seeded onto a 24-well plate (1 ϫ 10 5 cells/well) and grown in Sf-900 II serum-free medium (Invitrogen) overnight at 27°C. Cells were pWSSV-IE1 1-224 -V5-His IE1-F TCCCCGCGGATGGCCTTTAATTTTGAAGAC IE1-R TCCCCGCGGTACAAAGAATCCAGAAATCTCA pWSSV-GAL4-IE1 1-224 -V5-His IE1-F/IE1-R p35 BAS -Luc AcMNPV-p35-F1 CCGCTCGAGTGGCGACGGATTTTTATATACA AcMNPV-p35-R1 CCCAAGCTTTTTGCAATGGTAAAGCTCAAA G5p35 (30). The phRL/AcMNPVie1 plasmid contains the AcMNPV ie1 promoter to drive the expression of the Renilla luciferase gene and was used to monitor and normalize transfection efficiency.…”
Section: Plasmids (I) Luciferase Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of the switch between WSSV immediate-early, early, and late gene expression is largely unknown, and only two studies (16,24) have reported on the promoters and regulatory sequences that might be involved. An analysis of WSSV gene expression profiles in shrimp tissue showed that 37 of the 64 early genes (58%) and 28 of the 58 late genes (48%) contain a consensus TATA box [TATA(A/T)A] 0 to 300 nucleotides (nt) upstream of the translational start codon (29).…”
mentioning
confidence: 99%